Technological Change and Agricultural Labor Use - Delgado, Christopher L.; Ranade, Chandrashekhar G. (International Food Policy Research Institute, 1987)
The preceding chapters suggest three aspects of labor use in the agriculture of sub-Saharan Africa that are critical for the design and adoption of improved technology for increasing food production. First, both average and marginal labor productivity are generally low. Second, the agricultural environment is highly variable throughout the region, and labor productivity thus varies significantly, even across small areas. Third, labor inputs to African agriculture are sharply seasonal. Although returns to agricultural labor vary greatly across subregions, comparison of Africa with Asia suggests some common African features with respect to agricultural labor use. Low productivity and sharp seasonality in Africa may make technological change in African agriculture especially difficult compared to Asia, where smallholder technological change has been particularly successful.